Problematika Pembelajaran Pendidikan Agama Islam Pada Penyandang Tuna Grahita - Eko Hadi Wardoyo (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2021)
This study aims to find out the problems of learning Islamic religious education for people with mental retardation at SLB Hardika Bakti Tugusourcejo Peterongan Jombang. This research is qualitative, the data collection is done by interview, observation and documentation. While the data analysis is done by data reduction, data presentation and drawing conclusions. The results showed that: Mentally retarded children are children who have IQ barriers or can be socially impaired. The problems of learning Islamic religious education for mentally retarded persons are (1) the awareness of parents who can be both supporters and barriers to children's education. (2) mental retardation has mild, moderate, and severe levels with different levels of learning. (3) different characteristics of children. The solution is to hold parenting or discussions to find out what parents are complaining about so they can find a way out together and conduct visual education classes to find out the level of child development.